Diversity in Elementary Students’ Mathematical Problem-Solving Based on Polya’s Theory - Aan Nurhasanah; Tri Joko Raharjo; Sri Sumartiningsih; Barokah Isdaryanti (MASI Mandiri Edukasi, 2026)
This study aimed to describe elementary school students’ mathematical problem-solving abilities based on Polya’s problem-solving stages across different problem types (LOTS and HOTS) and school contexts. A descriptive quantitative design was employed involving 95 fourth-grade students from six elementary schools. Data were collected through a mathematical problem-solving test consisting of five essay questions developed according to Polya’s four stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The results showed that students achieved the highest performance in the plan stage (63.68%), followed by understanding the problem (60.05%), while lower achievement was observed in devising a plan (40.11%) and looking back (37.63%). The overall average problem-solving achievement was 50.37%. A comparison between LOTS and HOTS problems revealed that students consistently performed better on LOTS tasks across all Polya stages, whereas HOTS tasks presented substantial difficulties, particularly in planning solution strategies and evaluating answers. These findings indicate that procedural skills still dominate students’ mathematical problem-solving abilities, while strategic reasoning and reflective thinking remain underdeveloped. The study highlights the importance of instructional practices that explicitly support all stages of Polya’s framework through problem-based learning, mathematical justification, guided reflection, and differentiated instruction, thereby strengthening students’ problem-solving abilities.